Seasonal variation in the essential micro-nutrients of Gracilaria spp. of Tamil Nadu coast - Jayasankar, Reeta; Polywal, Kailash (Indian Journal of Fisheries, 2011)
Essential micro-nutrients such as manganese, copper, lead and zinc were analysed in three species of Gracilaria for 12 months from August 1994 to July, 1995. Comparative data on the interspecific variation of essential micro-nutrients have been explained. Seasonal variation of the trace element within the species were also analysed. Zinc content was found to be maximum in all the species of Gracilaria. In general, the decreasing trend of essential micro-nutrients was Zn>Pb>Cu>Mn. Manganese and copper content were found to be comparatively higher in G. edulis whereas lead dominated in G. crassa